Assessing the contribution of internal climate variability to anthropogenic changes in ice sheet volume. Issue 12 (29th June 2017) - Tsai, Chii‐Yun; Forest, Chris E.; Pollard, David
Abstract: Understanding ice sheet response to different sources of uncertainty in projecting the climate is essential for assessing long‐term risk of sea level rise (SLR). The impact of uncertainty caused by internal climate variability (ICV) on future ice sheet changes has not been assessed explicitly. Here we estimate how ICV affects ice sheet projections using a three‐dimensional ice sheet model driven by climate fields from two large ensembles of climate model simulations differing in initial climate states. We find that ICV causes approximately 2 mm uncertainty in the estimated SLR due to Greenland ice sheet mass loss during 1992–2011, which is nearly double the observational uncertainty. Additionally, SLR differences due to ICV are about 17% of the mean total change of SLR in 2100. This study highlights a critical need to assess uncertainties of projecting ice sheet loss due to ICV to obtain robust estimates of both historical and future SLR. Key Points: Internal climate variability can affect ice sheet contributions to sea level changes Using ensemble‐mean climate forcing can significantly underestimate ice sheet surface melt Internal climate variability can cause a 10 year window for detecting thresholds of sea level rise